Analisis Pengetahuan Ibu Hamil Tentang Epidemiologi dan Deteksi Dini Anemia Kehamilan dalam Pencegahan Stunting Balita di Desa Cikunir - Wuri Ratna Hidayani (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2026)
Pregnancy anemia was one of the risk factors for stunting in toddlers that needs to be watched out for and addressed. There were 24 pregnant women who did not undergo early detection of pregnancy anemia in Cikunir Village. This study was conducted due to low epidemiological knowledge and lack of participation of pregnant women in early detection of pregnancy anemia. This study is a descriptive study using qualitative methods, which was a continuation of previous studies. The population in this study was all pregnant women in Cikunir Village, with 8 pregnant women as the main informants. Data analysis used data triangulation with additional informants as sources of validation, namely 2 Posyandu cadres, 1 village midwife, and 1 head of the Singaparna Community Health Center. There were 8 informants and 4 sources of validation in this study. Purposive sampling was used and met the inclusion and exclusion criteria. Data analysis was carried out from the information obtained at the research data collection stage from the results of interviews using interview guidelines. This analysis used two variables, namely epidemiology and early detection of pregnancy anemia. Pregnant women stated that the epidemiology of pregnancy anemia was that the agent was blood deficiency, malnutrition, stress, the host is humans or pregnant women, and the environment was not consuming iron tablets, not consuming a balanced diet, low knowledge about pregnancy epidemiology, and behavior of not conducting early detection screening for pregnancy anemia. Preventive measures for pregnancy anemia include visiting a pregnancy facility. Pregnant women stated that they underwent prenatal check-ups twice a month, once a month, while some did not participate in prenatal check-ups. It is hoped that health services for pregnant women can be improved through education and active surveillance so that mothers who are unable to visit antenatal care can still receive antenatal care services